Estudos in vitro do bisfenol a na alteração fenotípica em tumor de mama e potencial transformante quando associado ao acetato de medroxiprogesterona - Luz, Felipe Andrés Cordero da (2016)
Bisphenol A (BPA) is a chemical compound with xenoestrogenic properties, acting as an endocrine disruptor, and contributes to tumorigenesis and tumor progression, and medroxyprogesterone acetate (MPA) is widely used in hormone replacement therapy and contraceptives. In several studies, these compounds where appointed as responsible for changes in proliferation, apoptosis resistance, cell migration and invasion, contribuitng to development and progression of breast cancer. In addition, recent studies observed that BPA can trigger epithelial-to-mesenchymal transition (EMT) in ER (estrogen receptor)+ and ER- cells through different pathways. In this two-branched study, triple-negative non-transformed mammary epithelial cells MCF-10A were long-term treated with micromolar concentrations of BPA, associated, or not, with acute treatment with MPA to analyze the tumorigenic properties of these two drugs in association (first branch); two breast cancer cell lines (MCF-7, ER+; MDA-MB-231, triple-negative) were used to observe EMT concomitantly with alternative splicing of FGFR2, chemoreceptors (CXCR2 and CXCR4), cancer stem cell (CSC) population, as well as MCF-7 cells resistance/sensibility to tamoxifen (second branch). In the first branch was observed that exposure to both BPA and MPA led to an invasive phenotype, with increased expression of CXCR4 and modification of splicing factors, and transition from epithelial to mesenchymal features, characterized by FGFR2 IIIc switch, increased VIM expression, and long-term augmented migration, as well as nuclear morphology alterations typical of cancerous cells; this is the first demonstration of a synergistic action of MPA in BPA pre-treated cells, leading normal cells to acquire malignant features by activating complementary cellular events associated with epithelial-mesenchymal transition, suggesting that environmental exposure to chemicals may increase the risk of cancer development, especially under hormonal therapies. In the second branch was observed EMT concomitantly with alternative splicing of FGFR2, chemoreceptors (CXCR2 and CXCR4), cancer stem cell (CSC) population, as well as MCF-7 cells resistance/sensibility to tamoxifen; results show striking differences between these cells: although BPA triggered EMT in the two cells, ER+ cells acquired more features involved with aggressiveness and resistance, suggesting that BPA may exert complications in ERα+ cancer.